METADISCOURSE MARKERS IN THE UNDERGRADUATE THESIS INTRODUCTION WRITTEN BY ENGLISH DEPARTMENT STUDENTS IN UNIVERSITY OF BENGKULU - Agustinos, Putri; Arsyad, Safnil; Syahrial, Syahrial (Journal of English Education and Teaching, 2018)
This research is aimed to find metadiscourse form and metadiscourse category which are dominantly used in the undergraduate thesis introduction written by English Department students of Bengkulu University. The documentation technique and checklist are used in this research. Fifteen undergraduate thesis introductions by English Department students were analyzed by using mix method quantitative and qualitative, along with descriptive approach. From the result it was found that English Department students dominantly used interactive metadiscourse markers category and transition metadiscourse markers form in their writing. However, English Department students used of metadiscourse markers were still limited to the use of and, or, also but metadiscourse markers.